(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
Abstract The myth was and is a source of inspiration for poets and writers from ancient literature to the present day. Samih al-Qasim is one of those poets who took inspiration from myth in his poetry and used it in a way that was consistent with his poetic, human and combative vision. In this research, we will stop at employing and drawing inspiration from the Greek myth in Samih Al-Qasim’s poetry, aiming with this to reach its symbolic and semantic dimensions, and to reveal its aesthetic connotations.